(untitled) (Research, Society and Development, 2020)
The aim of this research was to reflect on the influence of the media and the role of public security agencies in the face of the occurrences of missing persons. from 2010 to 2018. The methodology used was bibliographic research and documentary research. Among the main results, it was found: a) the role of the local media has been shown to be positive for the organization and cataloging of missing persons data; b) the media can act as a significant instrument for the dissemination of information and public campaigns and policies aimed at the population; c) in cases of disappearance of people, the media provides greater visibility before society, as well as before public security authorities. It was concluded that this study helped to understand the relevance of the role of the media in the event of cases of missing persons as it directs the performance of public security in the face of the phenomenon of the disappearance of people.